Human rights in combating organised crime and the problem of «illegal» migration in Europe - Kruessmann, Thomas (Journal of the Belarusian State University. Law, 2020)
The article analyses a number of legal problems related to the observance of human rights in the fight against transnational organised crime and illegal migration in Europe. The author highlights the features that distinguish human trafficking from illegal migration and raises a number of controversial issues related to the need to criminalise people smuggling, protect and promote the rights of migrants, establish responsibility for illegal entry and illegal residence, as well as the permissibility of criminalising by the assistance to migration by non-governmental organisations that conduct humanitarian search and rescue operations in the Mediterranean.
Keywords: transnational organised crime; human trafficking; migrant; smuggling of migrants; illegal migration